2019
DOI: 10.1002/ajhb.23275
|View full text |Cite
|
Sign up to set email alerts
|

Physical training over 6 months is associated with improved changes in phase angle, body composition, and blood glucose in healthy young males

Abstract: ObjectivesThe aim of this study was to evaluate the association between phase angle, body composition, and blood glucose changes in healthy young males after 6 months of physical training.MethodsVolunteers, 98 healthy males (18.8 ± 0.5 years), had 6 months of progressive physical training (5 days a week, 90 minutes a day). Resistance, reactance, and phase angle were obtained by bioelectrical impedance analysis, body composition (fat mass, bone mineral content [BMC], and lean soft tissue [LST]) by dual‐energy X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
3
10
0
Order By: Relevance
“…People with the highest physical activity had a higher mean phase angle than those with the lowest physical activity, but were also the youngest [11]. Similarly, longitudinal studies showed that the implementation of a physical activity program in non-athletes led to an increase in phase angle [12,13]. Interestingly, the phase angle values found in our runners are similar to the reference population data that we have published earlier [8].…”
Section: Discussionsupporting
confidence: 86%
“…People with the highest physical activity had a higher mean phase angle than those with the lowest physical activity, but were also the youngest [11]. Similarly, longitudinal studies showed that the implementation of a physical activity program in non-athletes led to an increase in phase angle [12,13]. Interestingly, the phase angle values found in our runners are similar to the reference population data that we have published earlier [8].…”
Section: Discussionsupporting
confidence: 86%
“…Muscle power was assessed by a supramaximal cycling test (Wingate) using a cycle ergometer (Monark ergomedic 894 E, Monark Exercise AB; Vansbro, Sweden), and CMJ, using a contact platform controlled by an open-source hardware and software model (Chronojump Boscosystems; Barcelona, Spain), as previously described [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Research in older adults has shown that RT increases PhA [ 10 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]; with similar results being observed in obese women [ 28 ], RT-trained women [ 29 ] and untrained young adults of both genders [ 30 ]. In addition, another study [ 31 ] conducted with young males (18.8 ± 0.5 years) showed improvements in PhA after 6 months of military training.…”
Section: Introductionmentioning
confidence: 98%
“…Before each session, all participants went through ~8 stretching exercises, ~7 neuromuscular warm-up, and ~7 general warm-up exercises. For sports training, each participant performed specific training for each modality [32,33].…”
Section: Military Physical Trainingmentioning
confidence: 99%